Sexual Dimorphism in Bokermannohyla martinsi (Bokermann, 1964) (Anura, Hylidae) with a Report of Male-Male Combat - Magalhaes, Rafael Felix de; Lacerda, Joao Victor A.; Reis, Luisa de Paula; Garcia, Paulo Christiano A.; Pinheiro, Paulo Duraes P. [UNESP] (Soc Brasileira Herpetologia, 2018)
Male-biased sexual size dimorphism (SSD), or a lack of SSD, in amphibians may be related to the territoriality. Male-biased SSD is quite abundant among the species of the Neotropical hylid genus Bokermannohyla. However, direct observations of territorial behaviour such as combat, suggestive of the presence of a male-biased SSD, are rare. We evaluated SSD in B. martinsi and provided a field record of a male-male combat event. We found males to have significantly wider forearm and longer tibia than females. It appears that male forearm hypertrophy is related to territoriality, but we cannot reject the possibility that it is an adaptation to breeding in lotic habitats. Finally, we emphasize the importance of direct natural history observations for understanding patterns of SSD among anurans in particular and amphibians in general.
Keywords: Espinhaco Mountain Range; Fighting call; Hypertrophied forearms; Intrasexual competition